+0  
 
-2
24
1
avatar

The function f satisfies f(n) = 3f(n - 2) - 2f(n - 1), where f(2) = 3 and f(1) = -1.  What is the value of f(5)?

 May 21, 2020
 #1
avatar+111321 
+1

f(n)  =  3f(n - 2)  - 2f(n - 1)

 

f(2)  =  3

 

f(1)  =  -1

 

f(3)  =  3f(3 - 2)  - 2f(3 - 1)   = 3f(1) - 2f(2)  =   3(-1)  - 2(3)  =  -3 - 6  =  - 9

 

f(4)  =  3f(4 - 2)  - 2f(4 - 1)  =  3f(2)  - 2f(3)  =  3(3)  - 2(-9)  =  9 + 18  =  27

 

f(5)  =  3f(5 - 2)   - 2f(5 - 1)  =  3f(3)  - 2f(4)  =  3(-9)  - 2(27)  =  -27 - 54  =  -81

 

 

cool cool cool

 
 May 21, 2020

3 Online Users